Pemilihan Obat Anti-Epilepsi (OAE) untuk Penyandang Epilepsi Wanita Usia Subur: Tinjauan Pustaka - Jenita Surianggo; Budi Riyanto Wreksoatmodjo (PT Kalbe Farma Tbk., 2025)
Epilepsy is the most common chronic brain disorder and can affect people of all ages. Globally, an estimated 60 million people are diagnosed with epilepsy, half of whom are women, and about a third of women with epilepsy are of childbearing age. The main therapy for epilepsy is anti-epileptic drugs to control epileptic seizures. In Indonesia, first-line anti-epileptic drugs are carbamazepine, valproic acid, phenobarbital, and phenytoin, while second-line anti-epileptic drugs are lamotrigine, levetiracetam, clobazam, and topiramate. There are many concerns when women with epilepsy start planning a pregnancy, especially regarding the effect of epilepsy drugs on pregnancy and their effects on the fetus, such as teratogenic effects, neonatal outcomes, and neurodevelopmental impacts. The choice of anti-epileptic drugs (AEDs) in women of childbearing age must be considered carefully.